2022
DOI: 10.2196/preprints.38340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deconstructing TikTok Videos on Mental Health: Cross-sectional, Descriptive Content Analysis (Preprint)

Abstract: BACKGROUND Social media platforms that are based on the creation of visual media, such as TikTok, are increasingly popular with adolescents. Online social media networks provide valuable opportunities to connect with each other to share experiences and strategies for health and wellness. OBJECTIVE The aim of this study was to describe the content of the hashtag #mentalhealth on TikTok. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The themes identified across signatures suggest users experience these communities as coping strategies for struggles with daily life that are not fully supported or recognized outside of TikTok. In this way, DID TikTok appears to share similarities with the kind of positive social support for mental illness that Basch et al (2022) and Russell et al (2021) have identified on the platform, which they suggest may have the potential to reduce stigma and encourage helpseeking behaviors. Still, affinities between users seemed primarily built on pointing toward a desire for affirmation within this community and a collective naming of DID experience, as opposed to a movement toward "treating" or "curing" illness.…”
Section: Exclusive Communitiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The themes identified across signatures suggest users experience these communities as coping strategies for struggles with daily life that are not fully supported or recognized outside of TikTok. In this way, DID TikTok appears to share similarities with the kind of positive social support for mental illness that Basch et al (2022) and Russell et al (2021) have identified on the platform, which they suggest may have the potential to reduce stigma and encourage helpseeking behaviors. Still, affinities between users seemed primarily built on pointing toward a desire for affirmation within this community and a collective naming of DID experience, as opposed to a movement toward "treating" or "curing" illness.…”
Section: Exclusive Communitiesmentioning
confidence: 91%
“…Scholarship suggests that mental health-related content on the platform is incredibly prevalent and receives high levels of engagement (Zenone et al, 2021). Much of this engagement is positive, with commenters offering social support, personal narratives, and advice (Basch et al, 2022). A recent content analysis of substance use disorder recovery videos on TikTok found that content creators depicted a strong social identity in recovery and offered social support to others.…”
Section: Tiktok and Mental Illnessmentioning
confidence: 99%